Ketahanan Pangan untuk Masa Depan: Integrasi Pendekatan Ekoteologis dan Teo-Sosiologis dalam Program Makan Bergizi Gratis di Indonesia - Yuda Septian Kurniawan; Muhammad Guntur; Suharyono (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
Indonesia’s Free Nutritious Meal Program (MBG) is a strategic initiative aimed at addressing malnutrition, reducing stunting, and strengthening sustainable national food security. This study explores the urgency and implementation of the program through theo-sociological and ecotheological perspectives by integrating Islamic values with principles of environmental responsibility. Employing a descriptive qualitative approach, the research analyzes public policy documents, hadith literature, and secondary data related to Indonesia’s nutritional conditions and stunting prevalence. The findings reveal that the effectiveness of the MBG Program depends not only on the provision of nutritious food but also on the integration of spiritual values, equitable food distribution, and environmentally sustainable food systems. The Islamic concept of halalan ṭayyiban provides a comprehensive ethical framework for ensuring food quality, nutritional adequacy, ecological sustainability, and social welfare. The study concludes that integrating theo-sociological and ecotheological approaches offers a holistic framework for enhancing the implementation of the MBG Program, contributing to food security, social justice, environmental stewardship, and long-term public health sustainability in Indonesia.